ENCEPHALOPATHY AND ENCEPHALITIS DUE ACUTE SARS-COV-2 INFECTION:: CASE REPORT - Moreira Rivelli, Álvaro; Maria de Oliveira Spindola, Gabriela; Eduarda da Silva, Luiza; Fernandes Mourão, Marcos (Health and Society, 2021)
Although Covid-19 disease is primarily considered an infection of the respiratory tract, it is currently known that damage and adverse reactions in the course of and after this disease affect several other bodily systems, however these issues are not yet fully understood, especially in tangent its neurological manifestations.3,4 In this sense, this report aims to add the list of many cases that are being reported/described in the literature which warn about the direct effects of the virus on the nervous system, to a disease for -infectious or post-infectious immune-mediated to COVID-19, such as acute disseminated encephalomyelitis, muscular diseases of the peripheral nervous system (Guillain-Barré syndrome), cerebrovascular and vascular diseases (CVA), and acute inflammatory processes such as that of the brain parenchyma in this case of Viral Encephalitis. Encephalitis is a diffuse or focal inflammatory process of the brain parenchyma associated with brain dysfunction, which can be divided into two main categories: alluding to systemic infections or vaccination and alluding to the entry of the pathogen into the CNS. Thus, based on the premise that several neurological manifestations are related to SARS-CoV-2 infection, a better understanding of the immune response to this infection can help not only for prevention but also can provide a valuable contribution to knowledge of the health-disease process, next human approaches, therapeutic and drug interventions